A Study of Corporate Digital Transformation and ESG Performance Based on the Moderating Effect of Female Executives - Can, Liao (Transactions on Economics, Business and Management Research, 2024)
The digital transformation and ESG performance of enterprises have gradually become key indicators of their high-quality development. Female executives, due to their different leadership styles and risk preferences compared to males, play a unique role in this process, but the specific mechanisms of these gender traits on enterprise high-quality development have not been fully studied. Therefore, this research focuses on A-share listed companies in China from 2018 to 2022, exploring the relationship between digital transformation and ESG performance, and the moderating role of female executives. The study further conducts subgroup analyses based on the nature of enterprise ownership and enterprise life cycle. The findings indicate that digital transformation has a lagging promoting effect on ESG performance, which is more significant in mature enterprises. The proportion of female executives negatively moderates this effect, particularly in state-owned and mature enterprises. Female executives' shareholding proportion inhibits this phenomenon, and this effect is more pronounced in non-state-owned enterprises. Compensation incentives have little impact on the moderation by female executives. This study provides a new perspective for the digital transformation and ESG practices of enterprises at the management level and enriches empirical evidence in the field of gender studies.